EFEKTIVITAS PENYULUHAN MENGGUNAKAN LAGU “GIGI SEHAT” TERHADAP PENURUNAN PLAK DI BARITO KUALA (Tinjauan SDN Barangas Timur 1 Kecamatan Alalak Kabupaten Barito Kuala) - Faulina Windiyana; Rosihan Adhani; Aulia Azizah (Dentin, 2020)
ABSTRAK           Background: Basic Health Research Results (Riskesdas) in 2018 showed the dental and oral health problems of the people in Indonesia reached 57.6%, while the dental and mouth problems in the province of South Kalimantan in children aged 5-9 years amounted to 71.17%, the daily brushing behavior amounted to 96.04% but the correct brushing time is only 4.97%. This indicates that there is still a lack of knowledge about how and when to brush the teeth properly and correctly so it needs an innovation in providing information in this is necessary. The counseling by using the songs is expected to change a person's behavior in ways and when they’re brushing their teeth properly. Objective: To analyze the effectiveness of the counseling using the "Healthy Teeth" song in students at the East Java 1 East Elementary School, Alalak District, Barito Kuala Regency. Method: Using an experimental and using the non equivalent control group design by dividing the respondents into two groups. The research was conducted at Barangas Blanket 1 Elementary School in Alalak Sub-district, Barito Kuala District, using the technique of probability sampling with positive sampling of 38 respondents. Results: The Whitney Mann test was found to have a significant significance of 0.018 <0.05, meaning that the effectiveness of using the "Healthy Teeth" song indeed decrease the index. Conclusion: Counseling using "Healthy Teeth" songs has effective effect in reducing plaque.Keywords: Counseling, Dental Plaque, SongABSTRAK          Latar belakang: Hasil Riset Kesehatan Dasar (Riskesdas) tahun 2018, masalah kesehatan gigi dan mulut masyarakat Indonesia sebesar 57,6%, sedangkan masalah gigi dan mulut di Provinsi Kalimantan selatan pada anak usia 5-9 tahun sebesar 71,17%, perilaku menyikat gigi setiap hari sebesar 96,04% tetapi waktu menyikat gigi yang benar hanya sebesar 4,97%. Hal tersebut menandakan bahwa masih kurangnya pengetahuan tentang cara dan waktu menyikat gigi yang baik dan benar sehingga perlunya suatu inovasi dalam memberikan informasi dalam hal tersebut. Penyuluhan menggunakan lagu diharapakan dapat merubah perilaku seseorang dalam cara dan waktu menyikat gigi yang baik dan benar. Tujuan: Menganalisis efektivitas penyuluhan menggunakan lagu “Gigi Sehat” pada siswa di SDN Barangas Timur 1 Kecamatan Alalak Kabupaten Barito Kuala. Metode: Menggunakan quasi eksperimental dengan rancangan non equivalent control grup design dengan membagi responden menjadi dua kelompok. Penelitian ini di laksanakan di SDN Barangas Timut 1 Kecamatan Alalak Kabupaten Barito Kuala dengan teknik pengambilan sampel menggunakan teknik non probability sampling dengan purposive sampling yaitu sebanyak 38 responden. Hasil: Uji Mann Whitney didapatkan nilai signifikansi sebesar 0,018 < 0,05, artinya terdapat efektivitas penyuluhan menggunakan lagu “Gigi Sehat” terhadap penurunan indeks plak. Kesimpulan: Penyuluhan menggunakan lagu “Gigi Sehat” efektif dalam menurunkan plak. Kata kunci:, lagu, penyuluhan, plak